Penerapan Diskusi Kelompok untuk Meningkatkan Hasil Belajar Siswa Kelas X DPIB SMK Negeri 1 Sumatera Barat pada Mapel PAI - Silvini Safitri (Jurnal Pendidikan Tuntas, 2024)
This study aims to improve student learning outcomes in Islamic Religious Education (PAI) subjects through the application of group discussion methods. This study used a Classroom Action Research (PTK) approach carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects were class X students of SMK Negeri 1 West Sumatra, totaling 20 people. Data were collected through learning outcome tests, observation sheets, and interviews. The results showed that the application of the group discussion method can improve student learning outcomes. In cycle I, the percentage of learning completeness reached 65%, while in cycle II it increased to 85%. In addition, group discussion also increased students' involvement in the learning process, as indicated by the increase in student activity observation scores. This method proved effective in encouraging collaboration, concept understanding, and students' critical thinking skills. Thus, the application of group discussion is recommended to be used as an alternative learning method in PAI subjects, especially to improve learning outcomes and student involvement in the teaching and learning process. Keywords: , ,